2016
DOI: 10.18352/ijca.214
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Judicial Staff and Court Performance: Evidence from Brazilian State Courts

Abstract: To handle the increasing caseload, the judicial systems of several countries have adopted three main strategies: changing norms and judicial procedures; investing in information and communication technologies; and hiring additional judicial staff. This paper investigates the impact of this third strategy on the performance of Brazilian courts. We use multiple regression analysis to test an array of related hypotheses about the complex interactions between the number of judicial staff and court productivity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 11 publications
0
23
0
9
Order By: Relevance
“…The available workforce has been mentioned as a positive factor to increase the judicial performance of courts (Chaparro & Jiménez, 1996;Gomes, Guimaraes, & Akutsu, 2016;Mitsopoulos & Pelagidis, 2007;Schneider, 2005). For instance, Chaparro and Jiménez (1996) found that a larger administrative workforce provides better working conditions for judges, while Mitsopoulos and Pelagidis (2007) found that good administrative support could help to speed the work of the courts.…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The available workforce has been mentioned as a positive factor to increase the judicial performance of courts (Chaparro & Jiménez, 1996;Gomes, Guimaraes, & Akutsu, 2016;Mitsopoulos & Pelagidis, 2007;Schneider, 2005). For instance, Chaparro and Jiménez (1996) found that a larger administrative workforce provides better working conditions for judges, while Mitsopoulos and Pelagidis (2007) found that good administrative support could help to speed the work of the courts.…”
Section: Hypothesismentioning
confidence: 99%
“…For instance, Chaparro and Jiménez (1996) found that a larger administrative workforce provides better working conditions for judges, while Mitsopoulos and Pelagidis (2007) found that good administrative support could help to speed the work of the courts. In the Brazilian Judiciary, Gomes, Guimaraes, and Akutsu (2016) used longitudinal data (2003to 2012 for all state courts to investigate the impact of hiring new judges and administrative assistants on court performance. The main findings indicate that the number of judicial assistants has a positive influence on court productivity, and the number of assistants mitigates the positive relationship between court caseload and court productivity.…”
Section: Hypothesismentioning
confidence: 99%
“…Anything that falls outside the jurisdiction of the Federal or the Special Justice is handled by the State System. The organizational standards of the judicial branch are defined in the Federal Constitution [9,20].…”
Section: Jurimetrics In the Context Of The Fredoom Of Information Actmentioning
confidence: 99%
“…Currently, the Brazilian judicial system has the following courts: the Federal Supreme Court (STF), the Superior Court of Justice (STJ), the Superior Military Court (STM), the Superior Labor Court (TST), the Superior Electoral Court (TSE), five Federal regional courts (TRFs), 24 Regional Labor Courts (TRTs), 27 Regional Electoral Courts, three State Military Courts of Justice (TJMs), and 27 State Courts of Justice (TJs) [20].…”
Section: Jurimetrics In the Context Of The Fredoom Of Information Actmentioning
confidence: 99%
“…Diversos estudos anteriores (Beenstock & Haitovksy, 2004;Castro, 2011;Gomes, Guimaraes, & Akutsu, 2016, 2017Souza & Schwengber, 2005) investigaram a relação entre força de trabalho e desempenho judicial, no entanto a relação entre congestionamento e força de trabalho praticamente não tem recebido atenção na literatura. Assim, a presente pesquisa busca suprir essa lacuna.…”
Section: Introductionunclassified